2020
DOI: 10.3389/fneur.2020.606923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rituximab in Chinese Children With Refractory Anti-NMDAR Encephalitis

Abstract: Purpose: To assess the efficacy and safety of rituximab treatment as second-line immunotherapy in pediatric cases of anti-NMDA receptor (NMDAR) encephalitis.Methods: We retrospectively recruited 8 patients with anti-NMDAR encephalitis who were treated with rituximab as second-line immunotherapy. We evaluated the clinical features, laboratory examination results and treatment protocols of the Chinese children and defined good outcomes based on the modified Rankin scale (mRS) score (0–2) at the last follow-up.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Antibodies against the N-methyl-d-aspartate receptor (NMDAR) are predominately of the IgG1 subclass (280). Patients with NMDAR encephalitis generally respond to rituximab, and in one case titers were undetectable post-treatment (152,239,(280)(281)(282). In an effort to enhance the effect of rituximab induction treatment, two non-randomized trials observed clinical benefit from repeated monthly dosing of rituximab in addition to induction dosing (283); and the addition of tocilizumab to rituximab (240).…”
Section: Nmdar Encephalitismentioning
confidence: 99%
“…Antibodies against the N-methyl-d-aspartate receptor (NMDAR) are predominately of the IgG1 subclass (280). Patients with NMDAR encephalitis generally respond to rituximab, and in one case titers were undetectable post-treatment (152,239,(280)(281)(282). In an effort to enhance the effect of rituximab induction treatment, two non-randomized trials observed clinical benefit from repeated monthly dosing of rituximab in addition to induction dosing (283); and the addition of tocilizumab to rituximab (240).…”
Section: Nmdar Encephalitismentioning
confidence: 99%
“…Fortunately, their treatment principles are generally similar, consisting of HIMP or IVIg. Notably, RTX is more likely to be used to treat anti-NMDAR encephalitis with an acute onset ( Dalmau et al, 2011 ; Dou et al, 2020 ; Thaler et al, 2021 ), but only in remission periods for maintenance treatment in MOGAD. We recommend that patients with MOGAD should be tracked and simultaneously tested for MOG-Ab and other antibodies in the serum and CSF for the early detection of an overlapping syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There has been studies on anti-NMDAR encephalitis being refractory to 1st line treatment but responded well to 2nd line immune therapy with minimal side effects like in our case. 13 The neurological presentation of SARS-CoV2 in the pediatric age group is still surfacing. We need to brace ourselves up with newer presentations as we are still in the middle of this pandemic situation which seems to linger on for some time.…”
Section: Discussionmentioning
confidence: 99%